Frequency of Neck Pain and Functional Disability Index among Undergraduate Physical Therapy Students of Bahawalpur, Pakistan - Muhammad Waqas Ghauri; Muhammad Hafeez; Shahid Raza; Hafiz Irshad Ahmed (Pakistan Journal of Medical Research, 2022)
The neck pain (NP), most prevalent musculoskeletal discomfort among the students is effecting physical and psychological wellbeing of an individual.1 This can result in weakness of scapular retractors, stretch weakness of trapezius, neural structure impingement (referred pain pattern) and tightness of anterior longitudinal structures, due to guarded posture of Neck.2 The old and new cases of neck pain worldwide are 16.7% to 75.1% in general population.3  The neck pain is not only caused by a single risk factor instead multiple risk factors could lead to the neck pain. These may be  biomechanical factors like inappropriate body alignment, wide degree of movement and its repetition, personal factors, neuromuscular factor, age and weight to height ratio.3  Among the musculoskeletal disorders,  38% of the elderly population is affected by neck pain, 6%  to 22 % of young population is affected with it in different geographical regions,4 while lifetime prevalence is 14.2 to 71%.5  In a cross-sectional study the frequency and lifetime occurrence in undergraduate participants was seen as 34.9%.6 In another study conducted in Peshawar, Pakistan, the frequency of neck pain was found to be 84% which is exceptionally high.7 In another study on 167 students it was found that 70.1% of the them were suffering from musculoskeletal pain.8 Students are more at risk of developing neck pain due to their prolong hours of sitting  and with poor angle of neck and trunk.9 The reason behind the study was that there is lack  of data on neck pain in students ............